Processing pathway effects in CoCrCuNi+X (Fe, Mn) high-entropy alloys. Issue 15 (3rd August 2019) - Derimow, N.; Clark, T.; Roach, C.; Mathaudhu, S.; Abbaschian, R.
ABSTRACT: A parallel study of mechanical alloying and solidification was carried out on FCC high-entropy alloys (HEAs) CoCrCuNi, CoCrCuFeNi and CoCrCuMnNi to investigate the effects of each processing methods on the resulting microstructure, crystal structure and microhardness. Elemental powders were mechanically alloyed followed by spark plasma sintering (SPS) at 800°C and 900°C to achieve densified discs, while arc melting was carried out from bulk pieces of the elemental metals followed by furnace annealing at 800°C and 900°C for 5 h. Both processing routes resulted in a primary FCC phase with secondary Cu-rich FCC segregation as interdendrites for the solidified alloys and particle boundaries for the SPS alloys, with the exception of a small amount of σ phase present in the SPS processed alloys. The solidification of the CoCrCuNi, CoCrCuFeNi and CoCrCuMnNi HEAs resulted in typical dendritic microstructure, followed by the precipitation of a small Cr-rich phase in the CoCrCuMnNi alloy after annealing. The grain size of the mechanically alloyed powder was approximately 20 nm from the Scherrers equation and the SPS processed HEAs consisted of a Cu-rich phase in the particle boundaries, forming cobblestone-like microstructure. The microhardness was examined in the as-cast, annealed and SPS states. It was found that the SPS processed samples had an increased microhardness by a factor of 2.5.